Can Fear of Movement, Depression and Functional Performance be a Predictor of Physical Activity Level in Patients With Knee Osteoarthritis? - Hasan KILINÇ,; Sevilay KARAHAN,; Bülent ATİLLA,; Gizem İrem KINIKLI, (Archives of Rheumatology, 2019)
Objectives: This study aims to explore whether fear of movement, depression and functional performance are predictors of physical activity levels in patients with knee osteoarthritis (OA). Patients and methods: A total of 200 patients (80 males, 120 females; mean age 53.23±5.99 years; range, 40 to 65 years) with knee OA participated in this cross-sectional, correlational-design study. Oxford Knee Score (OKS) was used to evaluate physical function and pain through patient perspective. Six-Minute Walk Test (6-MWT) was used to evaluate functional performance. International Physical Activity Questionnaire-Short Form (IPAQ-SF) was used to assess subjective physical activity level. A 17-item of the self-reported Tampa Scale for Kinesiophobia (TSK) questionnaire was used to determine the fear of movement level. Beck Depression Inventory (BDI) was used as a self-reported measure for depression level. Spearman correlation analysis and the linear regression model with R-square (R2) were used to correlate and explain the total variance. Results: International Physical Activity Questionnaire-Short Form was significantly correlated to OKS (r=-0.550), 6-MWT (r=-0.561), TSK (r=-0.693) and BDI (r=-0.429) in patients with OA (p<0.001). Linear regression analysis revealed that OKS, 6-MWT test, TSK and BDI were independently associated with IPAQ-SF in predicting physical activity level in patients with knee OA (p≤0.001; R2=0.621). Conclusion: This study increases the understanding of the predictors of physical activity level related to fear of movement, depression and functional performance in patients with knee OA. Improving physical activity levels in OA population is necessary to implement early treatment strategies before the disease progresses and more costly solutions are needed.